STRATEGI PENGEMBANGAN KAMPUNG BATU MALAKASARI SEBAGAI DAYA TARIK WISATA MINAT KHUSUS - Brahmanto, Erlangga; Hermawan, Hary; Hamzah, Faizal (Wahana Informasi Pariwisata : MEDIA WISATA, 2017)
Special interest tourism is one of the forms of attraction development recommended in the Regional Tourism Development Master Plan (RIPDA) of Bandung Regency. Therefore, realizing the special interest attraction of interest in Kampung Batu Malakasari destination is the most appropriate strategy in the development of the next destination. This article discusses how the strategy in developing Kampung Batu Malakasari to become a special interest tourist attraction. using qualitative studies and SWOT analysis resulted in several recommendations related to the strategy of developing special interest interest in Kampung Batu Malakasari, are: (1) Packaging special interest attractiveness; (2) Presenting geo-tourism based education (geowisata); (3) Provide staff training as a natural and cultural interpreter; (5 Improve accessibility to increase tourist comfort; (6) Involving citizens in tourism management with the concept of community-based tourism management. Keywords: Tourism attractions, special interest tourism, educational tourism, tourism